Modus of Artistic Biographies by M. Slaboshpytskiy - Chernysh, Anna (Pitannâ lìteraturoznavstva, 2013)
Artistic biography as special metagenre variety is examined in the article. In basis of biographic work is a hypothesis-model of life of hero-prototype. Writer-biographer, as a rule, in biographic works uses actively by diaries, memoirs, documents, protocols, newspaper and magazine publications, public appearances, that is instrumental in working out in detail of appearance of historical epoch and appearance of artist, and also tripping of with a plot canvas of works. On the example of novels-biographies of M. Slaboshpickiy “Maria Bashkirceva (Life Is After a Horoscope)”, “Todos’ Os’machka (Poet From Hell)”, “Nikifor Drovnyak”, “Self-portrait of Artist In Maturity” there is analysed psychological basis of works, and also the specific of genre of contaminations in the novels of the Ukrainian writer. For example, biographic novel-essay “Maria Bashkirceva (Life Is After a Horoscope)” and novel-biography “Poet From Hell (Todos’ Os’machka)” are examined from positions of psychological prose, in which intelligent fundamental psychological bars appearance of protagonists: a genotype, heredity, psychosomatic properties of artists, is artistically analysed, their temperament and others like that. Psychological basis of other biographic novels of M. Slaboshpickiy “Nikifor Drovnyakl” and “Self-portrait of Artist In Maturity” is artistically designed due to the reception of collage and contrasting with a plot editing which consists in the duty of events and psychical state of protagonists transition. The specific of text biographic roman-collage in which external and underlying structure formal express (experiments with a form, combinations with the artistic design of fact and device, inconsistence of composition structure, narrative manner, system of appearances, psychological basis, interpenetration of elements of the different semiotics systems) certify stylistic changes in text creation will be realized by such method, that mainly is determined the specific of collage, editing, shot off screen technique.